Teladan Ulama Batang Toru dan Angkola Barat Tapanuli Selatan - Khoirun Nikmad (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2021)
The formulation of the problem of this research is how the role models of the ulama of Batang Toru and Angkola Barat, South Tapanuli, in practicing religious values in the community, this type of research is field research with a qualitative approach. Data collection techniques in this study were observation, interviews, and documentation. The type of research is qualitative research, the time of this research has characteristics including setting and actual, the researcher is the key instrument, and the data is descriptive. This study concludes that the examples of the ulama of Batang Toru and Angkola Barat, South Tapanuli in religion are wara', friendly, polite, simple, firm, karomah, gentle and quiet. This example has become a zero model for the Muslim community of Batangtoru and West Angkola, while the challenge faced by the scholars is that they must continue to teach Islamic teachings even though not all people embrace Islam.